Inclusiveness Practices in Contemporary Feminist Narratives - Gohar Parissa Rahimi (Dive-In, 2023)
Feminisms have gained increasing visibility in the last decade, becoming part of public and media discourse in Western societies. The popularisation of gender discourses has been accompanied by the growing production of feminist guides, handbooks and manifestoes produced by journalists, influencers and celebrities to spread feminism among young women. Nevertheless, the actual articulations of feminist narratives are often intertwined with neoliberal postfeminist discourses on individualism that reinforce existing hierarchies of power. These narratives are opposed by others that question individualism and deconstruct existing power hierarchies. This paper explores the problematic outcomes of the feminist entanglement with neoliberalism, which result in the flattening of gender, race and class differences. Then, the neoliberal postfeminist dominant narrative is contrasted by and confronted with a critical analysis of two contemporary feminist manifestoes that, in different ways, oppose individualism and deconstruct existing power structures through intersectional inclusive practices.